Tindak Pidana Korupsi Tanah Kas Desa di Yogyakarta: (Studi Kasus Putusan Pengadilan Negeri Yogyakarta Nomor 8/Pid.Sustpk/2023/Pn Yyk) - Enrico Winadi; Benedictus Renny See; Antonius Maria Laot Kian (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This journal examines the criminal act of corruption related to village treasury land (tanah kas desa) in Yogyakarta, with a specific focus on the District Court Decision No. 8/Pid.Sus-TPK/2023/PN Yyk. The objectives are to identify the underlying reasons behind corruption practices, analyze the application of substantive criminal law, and assess the state losses as well as possible preventive measures for future land management. The study employs a qualitative research method through interviews, documentation, and literature review, involving key informants from the judiciary, prosecution office, police sector, and village administration. The findings reveal that corruption in village treasury land is driven by internal factors such as personal motives, economic background, moral integrity, legal awareness, and authority, as well as external factors including non-transparent bureaucracy, ingrained corruption culture, weak supervision, ineffective legal systems, and socio-economic pressures. The application of substantive criminal law is reflected in the assessment of elements of corruption, judicial considerations, and the interplay between legal norms, social impacts, and local wisdom. Furthermore, the study highlights significant economic and social losses, and recommends strategies for prevention, governance improvement, and strengthening accountability to minimize corruption risks in village land management.